(p)ppGpp-mediated GTP homeostasis ensures survival and antibiotic tolerance of Staphylococcus aureus - Andrea Salzer; Sophia Ingrassia; Parvati Iyer; Lisa Sauer; Johanna Rapp; Ronja Dobritz; Jennifer Müller; Hannes Link; Christiane Wolz (Communications Biology)
Abstract Antibiotic tolerance in non-growing bacterial populations is of major concern regarding antibiotic treatment failures. Whether and how the messenger molecule (p)ppGpp contributes to this phenomenon is controversial. We show for Staphylococcus aureus that (p)ppGpp-dependent restriction of the GTP pool is essential for the culturability of starved cells. Survival was independent of the GTP-responsive regulator CodY. Elevated GTP levels in a starved (p)ppGpp-deficient mutant led to quiescent state characterised by alterations in membrane architecture and a decrease of the proton motive force (PMF). This was accompanied by dysregulation of components involved in electron transport, including qoxABCD, encoding the main terminal oxidase. Increasing qoxABCD transcription by mutation of the transcription start site (iATP to iGTP) partially restored the culturability of the (p)ppGpp-deficient mutant. Thus, regulation of nucleotide-dependent promoters by altered nucleotide levels contribute to starvation adaptability. Loss of PMF under high GTP conditions also renders bacteria susceptible to antibiotics. Thus, targeting the PMF or nucleotide availability may be a valuable strategy to combat antibiotic tolerance.